A Review of Electroanalytical Techniques for Determination of Anti-HIV Drugs - Burçin Bozal; Bengi Uslu; Sibel A. Özkan (International Journal of Electrochemistry)
Until now after the human immunodeficiency virus (HIV) was discovered as the then tentative aetiological agent of acquired immune deficiency syndrome (AIDS), exactly 25 anti-HIV compounds have been formally approved for clinical use in the treatment of AIDS. These compounds fall into six categories: nucleoside reverse transcriptase inhibitors (NRTIs: zidovudine, didanosine, zalcitabine, lamivudine, abacavir, stavudine, and emtricitabine), nucleotide reverse transcriptase inhibitors (NtRTIs: tenofovir), nonnucleoside reverse transcriptase inhibitors (NNRTIs: efavirenz, nevirapine, delavirdine, and etravirine), protease inhibitors (PIs: ritonavir, indinavir, saquinavir, nelfinavir, amprenavir, lopinavir, fosamprenavir, atazanavir, tipranavir and darunavir), fusion inhibitors (FIs: enfuvirtide), coreceptor inhibitors (CRIs: maraviroc), and integrase inhibitors (INIs: raltegravir). The present paper submitted the use of various electroanalytical techniques for the determination of anti-HIV drugs. This paper covers the time period from 1990 to 2010 including voltammetric techniques that were reported. Presented application concerns analysis of anti-HIV drugs from pharmaceutical dosage forms and biological samples.